Implications of EU enlargement for the ACP: A discussion paper - European Research Office (Technical Centre for Agricultural and Rural Cooperation, 2004)
Major effects of incorporation into the CAP. According to the Commission, the incorporation of the ten ACs into the EU will result in a decrease in average tariffs in the ACs from 9% to 4%.